If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 2x + 5 = -15 Reorder the terms: 5 + 2x + 2x = -15 Combine like terms: 2x + 2x = 4x 5 + 4x = -15 Solving 5 + 4x = -15 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 4x = -15 + -5 Combine like terms: 5 + -5 = 0 0 + 4x = -15 + -5 4x = -15 + -5 Combine like terms: -15 + -5 = -20 4x = -20 Divide each side by '4'. x = -5 Simplifying x = -5
| 16-2r=3r+11 | | 12x=-45 | | 1x-5=3x+4 | | 10(-0.2X-1)=1/2(8X) | | 4(w+9)=4w-36 | | 162r=3r+11 | | p-67.5=24.1 | | 2w+16=6(w+6) | | 36=[4-y]3 | | (xy)^2/5 | | 0.15x^2-0.8x+1=0 | | 4/5×7 | | 5(x-3)=-9x-29 | | 0.5(4-8y)=5-3y | | 8=2x-12y | | 5x-1=x+15 | | 6a+2[a+6]=28 | | 4x+6+2x-10+3x+4=180 | | 27/50=x/100 | | 45A-7B=69 | | 6x+7+4x+23=90 | | 5k^2=-3k | | 8x-6-3x=x+7+x | | 2+3x=3x-8-x | | -16r-3r=36 | | -2(x-3)+6x=2x+3(x-4) | | 16r-3r=36 | | 4*x+5=-1 | | 0.5*x+3=13 | | 16r+3r=36 | | 2(4s+6)=60 | | -5(-3M-16)=-4(0.5M+1) |